Effects of solid base catalysts on depolymerization of alkali lignin for the production of phenolic monomer compounds. (September 2021) - Biswas, Bijoy; Kumar, Avnish; Krishna, Bhavya B.; Bhaskar, Thallada
Abstract: Different solid base catalysts such as CaO/CeO2, CaO/Al2 O3, and CaO/ZrO2 were used for the depolymerization of alkali lignin. Various reaction parameters including reaction solvents (ethanol and methanol), time (30, 60, 90 and 120 min) and catalyst amounts have been screened at reaction temperature of 180 °C. Catalytic liquefaction produced higher bio-oil yield and maximum bio-oil yield (50.0 wt%) was obtained with ethanol and methanol solvent using different catalysts (CaO/ZrO2, and CaO/CeO2 ). Non-catalytic reaction and support catalysts produced lower bio-oil yield (42.0–46.0 wt%). The bio-oil was analyzed using GC-MS, 1 H NMR, TOC, CHNS and FT-IR. It has been seen from the bio-oil analysis that vanillin was the main product with about 41.8–62.2 area%. This is due to solid base catalyst significantly enhancing the β-O-4 cleavage which increased the bio-oil yield as well as the selectivity of compound. The fundamental vibrations band at 2943 and 2978 cm −1 were observed for methoxy proton in catalytic bio-oil with higher intensity compared to the non-catalytic bio-oil. Maximum higher heating value (HHV) of bio-oil was observed with CaO/CeO2 catalyst with methanol solvent (27.6 MJ/kg). It is suggested that the energy of the bio-oil can be enhanced by CaO/CeO2 catalyst using methanol solvent for liquefaction reaction. Graphical abstract: Image 1